Medically important trombiculids: a systematic review of the global distribution and clinical consequences of their bites - Porras-Villamil, Julián F. (2021)
Background: Mites are among the smallest arthropods that can be seen without magnification, were the use of dermatoscopy is an invaluable tool. They are a cosmopolitan pest, and at the moment more than 250 species have been shown to produce problems for humans and animals alike. These mites are capable of producing a wide array of clinical signs and symptoms, from local to systemic, from mild to severe, as well as transmitting pathogens. This study aimed to provide an update to the clinical impact on human health, the distribution and species involved in the clinical conditions produced by trombiculids through a systematic review. Background: Mites are among the smallest arthropods that can be seen without magnification, were the use of dermatoscopy is an invaluable tool. They are a cosmopolitan pest, and at the moment more than 250 species have been shown to produce problems for humans and animals alike. These mites are capable of producing a wide array of clinical signs and symptoms, from local to systemic, from mild to severe, as well as transmitting pathogens. This study aimed to provide an update to the clinical impact on human health, the distribution and species involved in the clinical conditions produced by trombiculids through a systematic review. Methods: A systematic literature review was conducted in Medline, Lilacs, Redalyc, Scopus, SciELO and Google Scholar, were we use as a threshold of publication date the year 2008. We limited the search strategy to articles published in Portuguese, French, English and Spanish. Eligible studies were case reports and case series that reported outcomes in humans caused by trombiculid bites. Patient-level and study-level information was extracted. Results: The literature search yielded 832 studies; 13 were case reports, 4 case series and 2 descriptive studies reporting a total of 49 cases. Most patients were male, and the median age was 33.7±6.4 years old. The most frequently reported symptoms were local erythema, pruritus and papules. No deaths were documented. Trombiculids from the genera Trombicula, Eutrombicula and Leptotrombidium appear to be the most commonly reported. Discussion: Trombiculiasis is an infestation caused by the larval stage of various types of mites, known as chiggers, they belong to the class Arachnida and the family Trombiculidae. This systematic review provides an overview of the trombiculids of clinical importance, their distribution and effects of the bite on human health. Our results show that there are different species of mites that can have important consequences for human health. No fatal cases owere registered.Even so, the transmission of scrub typhus is important and remains one of the most life-threatening rickettsial infections in some regions of Asia. Conclusions: The bite of different species of trombiculids around the world can cause a wide array of clinical consequences to human health. Even as mortality appear to be nonexistent, trombiculid bites must be adequately diagnosed and treated properly: A systematic literature review was conducted in Medline, Lilacs, Redalyc, Scopus, SciELO and Google Scholar, were we use as a threshold of publication date the year 2008. We limited the search strategy to articles published in Portuguese, French, English and Spanish. Eligible studies were case reports and case series that reported outcomes in humans caused by trombiculid bites. Patient-level and study-level information was extracted. Results: The literature search yielded 832 studies; 13 were case reports, 4 case series and 2 descriptive studies reporting a total of 49 cases. Most patients were male, and the median age was 33.7±6.4 years old. The most frequently reported symptoms were local erythema, pruritus and papules. No deaths were documented. Trombiculids from the genera Trombicula, Eutrombicula and Leptotrombidium appear to be the most commonly reported. Discussion: Trombiculiasis is an infestation caused by the larval stage of various types of mites, known as chiggers, they belong to the class Arachnida and the family Trombiculidae. This systematic review provides an overview of the trombiculids of clinical importance, their distribution and effects of the bite on human health. Our results show that there are different species of mites that can have important consequences for human health. No fatal cases owere registered.Even so, the transmission of scrub typhus is important and remains one of the most life-threatening rickettsial infections in some regions of Asia. Conclusions: The bite of different species of trombiculids around the world can cause a wide array of clinical consequences to human health. Even as mortality appear to be nonexistent, trombiculid bites must be adequately diagnosed and treated properly.